The combination of HT-ac and HBET improves the cognitive and learning abilities of heat-stressed mice by maintaining mitochondrial function through the PKA–CREB–BDNF pathway. Issue 11 (18th May 2022) - Li, Hongxia; Xu, Xin; Cai, Mengyu; Qu, Yicui; Ren, Zifu; Ye, Chuyang; Shen, Hui
Abstract : The aim was to investigate whether the combination of hydroxytyrosol acetate (HT-ac) and ethyl β-hydroxybutyrate (HBET) can improve the cognition of heat-stressed mice, meanwhile exploring the mechanism of action. Abstract : The aim was to investigate whether the combination of hydroxytyrosol acetate (HT-ac) and ethyl β-hydroxybutyrate (HBET) can improve the cognition of heat-stressed mice, meanwhile exploring the mechanism of action. Mice were divided into 5 groups: control, heat-stressed, HT-ac, HBET, and HT-ac + HBET. Mice were gavaged for 21 days and exposed to heat (42.5 ± 0.5 °C, RH 60 ± 10%, 1 h day -1 ) on days 15–21, except for the control group. Results showed that the combination of HT-ac + HBET improved the cognitive and learning abilities of heat-stressed mice, which were tested by Morris water maze, shuttle box, and jumping stage tests. The combination of HT-ac + HBET maintained the integrity of neurons and mitochondria of heat-stressed mice. Likewise, this combination increased the mitochondrial membrane potential, the ATP content, the expression of phosphorylated PKA, BDNF, phosphorylated CREB and Bcl-2, and decreased the expression of Bax, caspase-3, and intracytoplasmic Cyt C in heat-stressed mice.